Factors Leading to an Unexpected Early Control of Covid-19 in Pakistan - Sarwat Jahan, Abdus Salam, Farrukh Ansar, Manzoor Khan, Syed Irfab Ullah, Sonia Javed, Sarwat Jahan, Abdus Salam, Farrukh Ansar, Manzoor Khan, Syed Irfab Ullah, Sonia Javed (Journal of Rawalpindi Medical College, 2022)
Introduction Different types of planning and strategies have been formulated following the up rise of Covid-19 in an attempt to limit the spread and to minimize both the crisis but the situation is still getting worse even in the developed states. Unexpectedly the rate of rise of Covid-19 declined after June 2020 in Pakistan and the slope decreased to 8,884 active cases out of 313,984 confirmed cases till September 2020. In addition to this unexpected decline, number of covid-19 related deaths. The fall in the covid-19 was unforeseen in this area and it led to the curiosity regarding the factors that were responsible for this scenario Methodology A country based research project was carried out in the Northwest School of Medicine for a period of 6 months. A sample group of 877 individuals of both the genders, age range from 15 to 80 years, belonging to various occupations, educational and socioeconomic backgrounds were included. Questionnaire on probable responsible factors for early control and shared with the participants. Results Most of the participants had an adequate level of knowledge and positive attitude towards Covid-19. The most prominent factor identified was the lack of stress and optimistic attitude. Conclusion The optimistic attitude and low stress levels not only decreased the disease spread but also reduced its morbidity level. Key words; Covid-19, unexpected control, morbidity, factors